GAMBARAN HISTOLOGI KELENJAR INTESTINAL PADA DUODENUM AYAM KAMPUNG (Gallus domesticus), MERPATI (Columba domesticus) DAN BEBEK (Anser anser domesticus)(Histological Feature of Intestinal Glands of Native Chicken (Gallus domesticus), Pigeon (Columba domesticus), and Duck (Anser anser domesticus)) - Zainuddin Zainuddin; Dian Masyita; Sarayulis Sarayulis; M. Jalaluddin; Erdiansyah Rahmi; Idawati Nasution (Jurnal Medika Veterinaria, 2016)
The aim of this research was to observe intestinal glands histology of duodenum from native chicken, pigeon, and duck. Samples used are duodenum from 3 native chickens, 3 pigeons, and 3 ducks with undifferentiated of sex and weight. Fowl was slaughtered, duodenum were taken out then proceeded for histology method using parraffination and stained with hematoxylin-eosin. Histological observation include the density and morphology of intestinal glands. Data were analyzed descriptively. The results showed that the intestinal glands histology differ among native chicken, pigeon, and duck but the morphology of intestinal gland was similar that was simple tubular. The number of intestinal glands in native chicken and pigeon almost similar and found in high density but lower than that found in pigeon. This difference assumed to be correlated with type and concentration of feed.